A new genus of African tiger moths, with a review of the Amsacta melanogastra Holland species group (Lepidoptera, Erebidae) - Dubatolov, Vladimir V. (Zootaxa, 2013)
The relationships of Afrotropical tiger moths remain relatively poorly analyzed (see Goodger & Watson 1995), despite some noticeable new generic descriptions (see Goodger & Watson 1995, Dubatolov 2006a, 2006b, 2009, 2009, Dubatolov & Haynes 2008). While studying series of tiger moths from the Natural History Museum and Manchester Museum, some specimens of “Diacrisia” epicaste Fawcett, 1915 (synonyms include “Spilosoma” occidentalis Bartel, 1903 and “Amsacta” melanogastra Holland, 1897) were found to have genitalia unlike any known Spilosomina genus, and are transferred to a newly described genus as follows.